Religious Diversity of Corporate Board and Firm Value: Evidence from South Korea - Kim, Wan-Yong (Religions, 2022)
When the board provides quality monitoring and advising to corporate managers, firms can achieve their goal, and so firm value increases. Board diversity is one of the issues that can affect the board effectiveness through influencing the quality of monitoring and advising. Hence, many prior studies have analyzed the effect of board diversity in various dimensions such as gender, age, race, ethnicity, education background on firm value or performance. However, prior studies do not reach out to the religious diversity of the board. So, this study investigates the relationship between religious diversity of the board and firm value. Using unique data of religion of directors for companies listed in Korea from 2008 to 2011, this study provides the following empirical results. In general, a high level of religious diversity has a positive impact on the firm value. However, when the degree of religious diversity of the board exceeds a certain point, religious diversity shows a negative relationship with the firm value. In addition, if the religion of directors is concentrated in one religion (when the level of diversity is low), firm value is lower than other control firms. The empirical finding of this study shows that religious diversity of the board matters in a similar way of other dimension of the board diversity.